Bio-patogenia de la difteria - Dasso, Héctor (1937)
1st The antitoxin of the serum does not effect the cure of diphtheria, but acts only on the originating toxin; 2rd That diphtheria is cured without anti-toxina (for those readers who are interesed in the subject, the existing abundant Bibliography and the treatment of diphtheria by diphtheric Haptinogenina is referred to); 3rd That the curative elements, which the serum introduces in the organism are heterogeneous, while these that the Haptinogenina provokes are isogeneous, to which difference is due the precocious, fundamental, and the persistent curative reaction of the Haptinogenina, in front of the retarded, artificial, and transitory reaction of the serum (Mendez). The argentine biological theory attains with the cure of diphtheria by Haptinogenina, the concluding proof, which demostrates that it is the only procedure which prevails or governs in the so-called toxemias and septicemias.